A Unified Treatment of the Relationship Between Ligand Substituents and Spin State in a Family of Iron(II) Complexes. Issue 13 (1st March 2016) - Kershaw Cook, Laurence J.; Kulmaczewski, Rafal; Mohammed, Rufeida; Dudley, Stephen; Barrett, Simon A.; Little, Marc A.; Deeth, Robert J.; Halcrow, Malcolm A.
Abstract: The influence of ligands on the spin state of a metal ion is of central importance for bioinorganic chemistry, and the production of base‐metal catalysts for synthesis applications. Complexes derived from [Fe(bpp)2 ] 2+ (bpp=2, 6‐dipyrazol‐1‐ylpyridine) can be high‐spin, low‐spin, or spin‐crossover (SCO) active depending on the ligand substituents. Plots of the SCO midpoint temperature ( T 1 / 2 ) in solution vs. the relevant Hammett parameter show that the low‐spin state of the complex is stabilized by electron‐withdrawing pyridyl ("X") substituents, but also by electron‐donating pyrazolyl ("Y") substituents. Moreover, when a subset of complexes with halogeno X or Y substituents is considered, the two sets of compounds instead show identical trends of a small reduction in T 1 / 2 for increasing substituent electronegativity. DFT calculations reproduce these disparate trends, which arise from competing influences of pyridyl and pyrazolyl ligand substituents on Fe‐L σ and π bonding. Abstract : Highs and lows : The low‐spin state of the complex shown is stabilized by electron‐withdrawing pyridyl "X" substituents, but also by electron‐donating pyrazolyl "Y" substituents. DFT calculations reproduce these results, which arise from competing influences of pyridyl and pyrazolyl ligand substituents on Fe−L σ and π bonding.